2011
DOI: 10.1007/s11368-011-0453-1
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) in marine sediments of the Hellenic coastal zone, eastern Mediterranean: levels, sources and toxicological significance

Abstract: Purpose Polycyclic aromatic hydrocarbons (PAHs) are widespread in sediments, particularly near areas of intense human activities. Due to their mutagenic and carcinogenic behaviour, PAHs are classified as priority contaminants to be monitored in environmental quality control schemes. The purpose of this study was to determine the levels of PAHs in major coastal areas of Greece that receive various pressures, investigate their sources and evaluate their potential toxicity by comparison against effects-based Sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 58 publications
1
23
1
Order By: Relevance
“…Colossal volumes of hazardous industrial waste have been disposed off into the Gulf for over half a century (Bearzi et al, ; Issaris et al, ). Although the disposal of red mud at sea stopped in 2011 (Issaris et al, ; http://www.alhellas.com), contamination through the food web may expose dolphins to the immunotoxic and other detrimental effects of persistent environmental pollutants (Botsou & Hatzianestis, ; Desforges et al, ; Jepson et al, ; Malea, Haritonidis, & Kevrekidis, ; Tsangaris et al, ). Preferred dolphin habitat overlaps with areas of red mud disposal and dolphins show no avoidance of red mud areas (Bearzi et al, ), as further documented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Colossal volumes of hazardous industrial waste have been disposed off into the Gulf for over half a century (Bearzi et al, ; Issaris et al, ). Although the disposal of red mud at sea stopped in 2011 (Issaris et al, ; http://www.alhellas.com), contamination through the food web may expose dolphins to the immunotoxic and other detrimental effects of persistent environmental pollutants (Botsou & Hatzianestis, ; Desforges et al, ; Jepson et al, ; Malea, Haritonidis, & Kevrekidis, ; Tsangaris et al, ). Preferred dolphin habitat overlaps with areas of red mud disposal and dolphins show no avoidance of red mud areas (Bearzi et al, ), as further documented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Aliphatic hydrocarbons and PAHs have been investigated over the last decades in surficial sediments of the EMS, primarily in coastal or shallow basin sites in the Aegean Sea, southern Italy, the coast of Egypt and the Adriatic Sea (Aboul-Kassim and Simoneit, 1995;Alebic-Juretic, 2011;Botsou and Hatzianestis, 2012;Cardellicchio et al, 2007;Gogou et al, 2000;Gonul and Kucuksezgin, 2012;Guzzella and De Paolis, 1994;Marcomini et al, 1986;Nemr et al, 2007;Sklivagou et al, 2008;Yilmaz et al, 1998). However, there is an important lack of data regarding their occurrence in deep basins, which might represent a long-term sink for hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Although Botsou and Hatzianestis (2012) reported that the current site receives the impact of human activities, the fish-mussel farm is located to a close gulf (Gulf of Kontinova) which is far away from any human activities and is characterized by negligible levels of inorganic and organic pollution (Banakou and Dailianis, 2010;Chatziargyriou and Dailianis, 2010;Giannapas et al, 2012;Kalpaxis et al, 2004). The collected mussels were transferred to the laboratory and maintained for 7 days in static tanks, containing re-circulated UV-sterilized and filtered artificial seawater (ASW; pH 7.9 AE 0.4, salinity 36 AE 1&, temperature 15 AE 1 C, dissolved oxygen 7 AE 0.5 mg L À1 ), with a 14:10 h light: dark photoperiod, in order to be acclimated in laboratory conditions.…”
Section: Mussel Collection and Handlingmentioning
confidence: 99%